TIGA PARADIGMA EVALUASI PENDIDIKAN: SEBUAH PETA PERKEMBANGAN - Agung Prihantoro (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
In the field of classroom educational assessment or evaluation, there is a research gap in the development of three educational assessment paradigms: assessment of learning, assessment for learning, and assessment as learning. The paper aims to fill the gap by describing the development. The research methodology employed was literature review. The results indicated that two phases of the development are early and advanced ones. In the early phase, some educational stakeholders hoped to orient educational assessment toward learning, not only assessing. The early phase originated the assessment as learning which showed differences among the three paradigms. In the advanced phase, the assessment as learning together with the assessment of learning and the assessment for learning were applied in various classes in schools and higher education in many countries. The application generated scientifically empirical shreds of evidence of strengths and weaknesses and future progress of particularly the assessment as learning.